How Strategies and Challenges Affect the Realization of Local Original Revenue Target in the Laboratory UPTD of the Public Works and Public Housing Service of Cilacap Regency - Dyah Ayu Subekti; Kartini , Kartini (International Journal of Economics and Management Sciences, 2025)
This study aims to analyze how internal strategies and external challenges can influence the achievement of Regional Original Revenue targets at the Laboratory Technical Implementation Unit (UPTD) of the Public Works and Public Housing Agency (Dinas Pekerjaan Umum dan Perumahan Rakyat) of Cilacap Regency. The research object is the performance of the Laboratory Technical Implementation Unit (UPTD), a technical unit providing construction material testing services, which directly contributes to Regional Original Revenue in Cilacap Regency. The qualitative approach employed a case study method, and data collection techniques included interviews, observation, and documentation. The sample in this study was obtained purposively. The results indicate that internal strategies focused on superior testing methods such as core drilling, abrasion, and concrete compressive strength have been conducted. However, limited equipment, human resources, and the lack of accreditation are major obstacles. On the other hand, external challenges include the lack of updated Regional Regulation tariff regulations, the absence of formal obligations for the use of laboratory services for regional budget projects, and a saturated local market. These findings provide important implications for the Laboratory Technical Implementation Unit (UPTD) in emphasizing policy revisions, increasing internal capacity, and strengthening inter-agency coordination to increase Regional Original Revenue realization.